Highly efficient solution-processed thermally activated delayed fluorescence emitter based on a fused difluoroboron ketoiminate acceptor: C/N switch to realize the effective modulation of luminescence behavior. Issue 40 (13th October 2021) - Wang, Xin; Li, Hua; Wu, Xiaofu; Shu, Haiyang; Tian, Hongkun; Tong, Hui; Wang, Lixiang
Abstract : Through simple C/N switching, the 3 LE state of the two emitters can be drastically changed. Accordingly, a fluorescent molecule (DMAC-FBKI ) can be transformed into a highly efficient TADF emitter (DMAC-aza-FBKI ). Abstract : Thermally activated delayed fluorescent (TADF) materials based tetracoordinate boron acceptors hold great potential for organic light emitting diode (OLED) applications; however, these emitters suffer from a low luminescent efficiency ( Φ PL ) and a large device efficiency roll-off. Herein, we design and synthesize two D–A-type emitters based on two fused boron ketoiminate (FBKI and aza-FBKI ) acceptors and a 9, 9-dimethylacridine (DMAC) donor. Through changing the carbon atom to a nitrogen atom in the fused boron ketoiminate units, a conventional fluorescent molecule (DMAC-FBKI ) can be transformed into a highly efficient TADF molecule (DMAC-aza-FBKI ) due to the dramatically reduced Δ E ST (0.46–0.04 eV). DMAC-aza-FBKI exhibits a short delay lifetime of 2.2 μs and a large reverse intersystem crossing rate constant ( k RISC ≈ 1.5 × 10 6 s −1 ), which is attributed to the rather close energy levels of its 3 LE, 3 CT and 1 CT states based on theoretical calculations. Furthermore, compared with DMAC-FBKI ( Φ PL ≈ 44%), DMAC-aza-FBKI has a higher Φ PL of 82% due to the existence of intramolecular hydrogen bonding. Consequently, the corresponding electroluminescent device achieves the highest external quantum efficiency (EQE) of 16.2% and an efficiency roll-off of only 9.3% at 1000 cd m −2, which are much better than those of the device based on the TADF-inactive DMAC-FBKI .